Inducible engineering precursor metabolic flux for synthesizing hyaluronic acid of customized molecular weight in Streptococcus zooepidemicus - Rui Zhao; Jun Li; Yingtian Li; Xujuan Pei; Jingyi Di; Zhoujie Xie; Hao Liu; Weixia Gao (Microbial Cell Factories)
Abstract Background Hyaluronic acid (HA) is extensively employed in various fields such as medicine, cosmetics, food, etc. The molecular weight (MW) of HA is crucial for its biological functions. Streptococcus zooepidemicus, a prominent HA industrial producer, naturally synthetizes HA with high MW. Currently, few effective approaches exist for the direct and precise regulation of HA MW through a one-step fermentation process, and S. zooepidemicus lacks metabolic regulatory elements with varying intensities. The ratio of HA’s precursors, UDP-N-acetylglucosamine (UDP-GlcNAc) and UDP-glucuronic acid (UDP-GlcA), is critical for the extension and release of HA. An imbalance in the precursor proportions for HA synthesis leads to a significant decrease in HA MW, indicating that controlling the precursor ratio may serve as a potential method for regulating HA MW. Results In this study, the type and concentration of carbon sources were manipulated to disrupt the balance of precursor supply. Based on the results, it was speculated that the transcription level of hasE, which may connect the two HA synthesis precursors, is positively correlated with HA MW. Consequently, an endogenous expression component library for S. zooepidemicus was constructed, comprising 32 constitutive and 4 inducible expression elements. The expression of hasE was subsequently regulated in strain SE0 (S12 ΔhasE) using two constitutive promoters of differing strengths. The recombinant strain SE1, in which hasE was controlled by the stronger promoter PR31, produced HA with a MW of 1.96 MDa. In contrast, SE2, utilizing the weaker promoter PR22, synthesized shorter HA with a MW of 1.63 MDa, thereby verifying the hypothesis. Finally, to precisely regulate HA MW according to specific demands, an efficient sucrose-induced expression system was screened and employed to control the transcription level of hasE, obtaining recombinant strain SE3. When induced with sucrose concentrations of 3, 5–10 g/L, the HA MW of SE3 reached 0.78 to 1.77 MDa, respectively. Conclusions Studies on regulating the balance of the HA precursor substances indicate that an oversupply of either UDP-GlcNAc or UDP-GlcUA can reduce HA MW. The hasE gene serves as a crucial regulator for maintaining this balance. Precise regulation of hasE transcription was achieved through an efficient inducible expression system, enabling the customized production of HA with specific MW. The HA MW of strain SE3 can be accurately manipulated by adjusting sucrose concentration, establishing a novel strategy for customized HA fermentation. Graphical Abstract